Optimalisasi Grafena dalam Pengembangan Baterai Ramah Lingkungan Berkapasitas Tinggi - Iksan Arif Munandar; Ryan Sadewo; Ammar Mustaqim; Arfan Pratama; Shalahuddin Hafizd Al Aziz (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Graphene is a two-dimensional lattice made of a single carbon atom and has extraordinary mechanical, electrical and thermal properties. These properties make it a very important material for a variety of applications, including energy management and electronics. This research adopts a systematic literature review approach to evaluate the role of graphene in improving battery performance and environmental sustainability. The results show that graphene significantly improves the performance of lithium-ion and lithium-sulfur batteries as well as sodium and magnesium-based batteries. In addition, graphene also has great potential for environmental applications such as water purification and pollutant adsorption. However, challenges such as production costs, toxicity, and scalability still need to be overcome for wider adoption.